Pengaruh Total Quality Management, teknologi dan budaya organisasi terhadap kinerja manajerial - Apip Alansori; Erna Listyaningsih; Yuliansyah Yuliansyah; Iing Lukman; Eka Sariningsih (Jurnal Akuntansi, Keuangan, dan Manajemen, 2021)
Purpose: To find out how much influence the managerial performance has in managing MSMEs and how capable it is in implementing Total Quality Management, technology and organizational culture in increasing MSMEs income. Research methodology: This research is a qualitative research with a case study approach. The data survey method used was research using probability sampling, Partial Least Square (PLS), Average Variance Extracted (AVE, Coefficient of Determination and Path Coefficient Test and Banana Chips MSME on Street Pagar Alam Bandar Lampung. Results: Total Quality Management, technology, and organizational culture simultaneously have a significant influence on managerial performance. Limitations: Time and number of research samples. Contribution: In the MSMEs environment, the natural fence road in Bandar Lampung and local government related to MSMEs Keywords: Total Quality Management, Technology, Organizational culture, Managerial performance, MSMEs